Antecedents of Work Related Expectancies - Sims, Henry P.; Szilagyi, Andrew D.; McKemey, Dale R. (Academy of Management Journal, 1976)
This research investigated the environmental antecedents of expectancy I and expectancy II. Expectancy II was found to be strongly related to supervisory variables and, to a lesser extent, to organization practices variables. Expectancy I was mildly related to organization practices variables. Internal control individuals had stronger El and Ell perceptions. Implications for management development and training are discussed.